Phylogenomics of the Neotropical fish family Serrasalmidae with a novel intrafamilial classification (Teleostei: Characiformes) - Mateussi, Nadayca T. B. [UNESP]; Melo, Bruno F. [UNESP]; Ota, Rafaela P.; Roxo, Fabio F. [UNESP]; Ochoa, Luz E.; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Elsevier B.V., 2020)
The Neotropical fish family Serrasalmidae comprises 16 extant genera and 101 species widespread through major Neotropical rivers with relevant importance for regional fisheries and aquaculture. The monophyly of Serrasalmidae and the recognition of three main clades are recurrent between morphological and molecular phylogenies. However, both intergeneric and interspecific relationships within each of those clades remain uncertain. Here, we used 81 terminals of 69 species (68%) and all 16 genera of Serrasalmidae to sequence 1553 loci of ultraconserved elements (UCEs), multiple nuclear loci widely applied in phylogenetic studies, and performed maximum likelihood, Bayesian, and species tree analyses. We obtained highly supported phylogenies in all applied methods corroborating the monophyly of Serrasalmidae and the three-clade hypotheses herein proposed as two subfamilies and two tribes: (Colossomatinae (Serrasalminae (Myleini + Serrasalmini))). Morphological features for each subfamily involve the absence (Colossomatinae) or presence (Serrasalminae) of a pre-dorsal spine. Morphological diagnoses among tribes include the pre-dorsal spine being continuous (Myleini) or discontinuous (Serrasalmini) relative to the first unbranched dorsal-fin ray. Our results highlight the complexity of the relationships especially the non-monophyly of Myleus, Mylesinus, Myloplus, Tometes, and Utiaritichthys within Myleini, as well as of Serrasalmus and Pristobrycon within Serrasalmini.
Keywords: Biodiversity; Ostariophysi; Pacu; Piranha; South America; Ultraconserved elements